The Effectiveness of the Buerger Allen Exercise Intervention on Changes in Ankle Brachial Index Values in Diabetes Mellitus Patients: Literature Study - Fatima Ura Pabanne (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Research is a literature study. In the strategy of looking for journals, the framework used is PICOT. The keywords used were "Buerger Allen exercise AND Ankle Brachial Index Value AND Diabetes Mellitus Patients". The data sources used are the e-resources database of the National Library, Pubmed and Google Scholar in the form of articles or journals. The inclusion criteria in this study were national and international journals from different databases and related to research variables, namely the Buerger Allen exercise and the Ankle Brachial Index Value in Diabetes Mellitus Patients and the article publication deadline within the last 5 years. (2016-2021). The exclusion criteria for this study were national and international journals from different databases and had nothing to do with research variables, no intervention was given, there was no effect of the Ankle Brachial Index Value in Diabetes Mellitus Patients and the time of publication of articles was more than 5 years. In search The article search used 3 databases, each found from National Library of Indonesia 219 search results, PubMed 458 search results and Google Scholar 1236 search results. After being disqualified regarding the year of publication, namely the last 5 years and selecting duplicate articles, 327 articles were obtained, and finally 6 articles that met the criteria. Of the 6 articles that have been reviewed and found, most patients with kidney failure experience changes in quality of life. Based on a literature review of 6 research journals, it can be concluded that the Buerger Allen exercise is effective in reducing changes in the value of the ankle brachial index in patients with diabetes mellitus..